Distribuição de Euterpe edulis Martius na Mata Atlântica revela diferentes níveis de variabilidade genética : implicações para a conservação - Pereira, Aléxia Gonçalves (2019)
Euterpe edulis, known as the heart palm, is a key species of the Atlantic Forest, recorded in different phytophysiognomies. It is categorized as vulnerable to extinction due to loss of habitat, fragmentation and exploitation of the heart palm, which is of great gastronomic interest. Even considering this situation, studies with molecular markers has shown high diversity, low index for endogamy and genetic structuring. In search of answers about the distribution of the genetic diversity and the structure of this species in the Atlantic Forest, this study analyzed 26 variables and 527 individuals along the biome. The samples were collected from important national and international Conservation Units, RPPNs and fragments containing a minimum of 15 adult individuals. Eight SSR molecular markers were used to verify the existence of an inter and intrapopulation and evaluate the species structuring. Considering all the individuals analyzed, the study found out a loss of genetic diversity (He = 0.87 and Ho = 0.49) and high inbreeding (F = 0.43). The Southeast and the Midwest presented the largest Ho while the Northeast presented the smaller, thus being the most inbred region. The states of Minas Gerais, Federal District and Rio de Janeiro presented the highest frequencies in Ho, with Espírito Santo, Bahia and Paraná, with the highest rates of inbreeding. Analyzing by populations, He ranged from 0.48 to 0.79, Ho ranged from 0.30 to 0.63. The highest indexes of fixation (F) belong to VALE - ES Natural Reserve (0.60), Iguaçu National Park - PR (0,46), Serra da Jibóia - BA (0,46) and Parna da Serra da Bocaina - RJ (0.44), these being the highest values reported in the literature. This result represents a natural recovery process after the exploitation process, associated with the foraging behavior of pollinators and the absence of large seed dispersers. The maintenance process carried out by conservation units allowed the necessary response time for a species to genetically imprints the pressures it undergoes. Genetic variation between plants by FST and AMOVA was low, although analyzes by STRUCURE and PCoA demonstrated an initial deforestation process for a species within geographic regions. It was also possible to identify populations with unique genetic compositions, such as in the Serra Talhada National Park and the Murici Ecological Station in Alagoas; the RPPN VERACEL Station and the Serra da Jibóia - Jequitibá Reserve in Bahia; IBGE Ecological Reserve in Brasília, Itapeva State Park and Mata Paludosa Biological Reserve in Rio Grande do Sul. These populations may increase the variation for conservation and pre-improvement programs.